Polyvinyl alcohol-alginate adsorbent beads for chromium (vi) removal - Lee, Te Chuan; Manap, Norpadzlihatun; Abdullah, Hasan Zuhudi; Idris, Maizlinda Izwana (Science Publishing Corporation (SPC), 2018)
Chromium pollution has been an increasing concern worldwide because of its high toxicity and carcinogenic properties, and it requires an efficient purification technique. In this study, adsorbent beads containing polyvinyl alcohol (PVA) and sodium alginate were prepared by crosslinking with boric acid and calcium chloride for adsorbent of the hexavalent chromium [Cr (VI)]. Batch adsorption studies were conducted to evaluate Cr (VI) adsorption rates of PVA-alginate beads from aqueous solution under ultraviolet (UV) light illumination. The surface morphology and elemental composition of beads were examined using field emission scanning electron microscopy (FESEM) and energy dispersive spectrometer (EDS), respectively. This study revealed that the Cr (VI) adsorption rates increased remarkably with dosages of PVA and sodium alginate. This occurred mainly due to the increasing number of the active sites for adsorption. The results revealed that adsorbent beads with 12 g of PVA and 2.5 g sodium alginate beads exhibited superior Cr (VI) adsorption efficiency at which it is completely removed after 1.5 hours. The findings of this study indicate that PVA-sodium alginate beads are a viable option for Cr (VI) removal from industrial wastewater.